THE DEVELOPMENT OF ETHNOSCIENCE BASED HIGH SCHOOL PHYSICS ENRICHMENT BOOK IN THE TRADITIONAL PROCESSING OF NUR KERINCI COFFEE - Jufrida Jufrida; Wawan Kurniawan; Vetty Milyani; Fibrika Rahmat Basuki (ScienceEdu, 2021)
This research is development research that aims to develop an ethnoscience-based high school physics enrichment book on the traditional processing of Nur Kerinci coffee and to find out the students’ perceptions about the enrichment book. The subjects of this study were material experts, media experts, and class XII MIPA 1 students of SMAN 11 Kota Jambi, totaling 24 students. The instruments used in this study were observation sheets, interview sheets, expert validation sheets, student perception questionnaires, and documentation. The resulting data are in the form of qualitative and quantitative data. Qualitative data were analyzed descriptively and quantitative data were analyzed using descriptive statistics. Local wisdom in the form of traditional processing of Nur Kerinci coffee is used as a context for the problem to explore scientific concepts, especially physics concepts. The results of the material expert validation obtained an average score of 93.33% with the "very good" category and the media expert at 93.33% with the "very good" category. Meanwhile, the results of the student perception trial obtained an average score percentage of 89.53% in the "very good" category.